Impact of Excess Body Weight on Health-Related Quality of Life Among Adults in Lebanon - Abbas, Linda Abou; Haidari, Rana El; Hassan, Khodor Haidar (European Scientific Journal, ESJ, 2019)
The objective of this study is to evaluate the impact of excess body weight on Health-Related Quality of Life (HRQoL). A convenience sample of 320 adults was recruited from different health centers in Lebanon. Body mass index (kg/m2 ) was calculated based on measured weight and height. Participants were divided into three groups: normal-weight (18.5-24.9), overweight (25.0-29.9) and obese (≥30.0). HRQoL was assessed using the Short-Form health survey questionnaire (SF-36). The eight scales as well as the physical (PCS-36) and mental (MCS-36) component summary measures of the SF-36 were calculated and compared statistically among the three groups. The impact of Body Mass Index (BMI) on HRQoL was also examined through linear regressions, adjusting for sociodemographics, health behaviors and presence of chronic diseases. The results show that overweight and obese men reported reduced HRQoL on all physical scales, while overweight/obese women reported impairments on only two subscales: bodily pain and general health perceptions. PCS-36 showed lower scores in the obese and overweight subjects than the reference group. With regard to mental well-being, obese men and women displayed lower scores on vitality, social functioning and mental health subscales compared to the normalweight group. Additionally, MCS-36 showed lower scores in obese subjects. Results from linear regressions revealed significant negative correlations between BMI and both PCS-36 and MCS-36. In conclusion, overweight adults experience significantly worse physical HRQoL, while obese adults suffer from reduced physical and mental HRQoL. This highlights the importance of development and implementation of effective prevention strategies to improve HRQoL among adults with overweight and obesity.